Electromagnetic wave effects on interfacial tension of co-doped iron oxide nanofluid - Hamid, Mohamad Amin; Hoe Guan, Beh; Kar Tim, Chan; Soleimani, Hassan (Elsevier B.V., 2024)
The influence of electromagnetic waves on the interfacial tension of cobalt-doped iron oxide nanofluids is investigated in this study. Co-doping in iron oxide nanoparticles changes their magnetic properties, turning them into hard magnets. This, in turn, impacts their interfacial behaviour when exposed to electromagnetic fields. A comprehensive examination of the structural and magnetic properties is conducted on cobalt-doped iron oxide synthesized using the co-precipitation method. Our results indicate a reduction in interfacial tension when electromagnetic fields are applied, using both direct current and alternating current, suggesting potential applications in controlled drug release and enhanced oil recovery processes.